The role of SCF ubiquitin-ligase complex at the beginning of life - Jiayan Xie; Yimei Jin; Guang Wang (BMC, 2019)
Abstract As the largest family of E3 ligases, the Skp1-cullin 1-F-box (SCF) E3 ligase complex is comprised of Cullins, Skp1 and F-box proteins. And the SCF E3 ubiquitin ligases play an important role in regulating critical cellular processes, which promote degradation of many cellular proteins, including signal transducers, cell cycle regulators, and transcription factors. We review the biological roles of the SCF ubiquitin-ligase complex in gametogenesis, oocyte-to-embryo transition, embryo development and the regulation for estrogen and progestin. We find that researches about the SCF ubiquitin-ligase complex at the beginning of life are not comprehensive, thus more in-depth researches will promote its eventual clinical application.